PELATIHAN PARALEGAL DESA MOLAMAHU KECAMATAN PULUBALA (PELATIHAN PARALEGAL SEBAGAI WAHANA PENINGKATAN PARTISIPASI AKTIF MASYARAKAT DESA DALAM PENEGAKAN HUKUM) - Martam, Nurmin K.; Hanapi, Yayan (Universitas Gorontalo, 2026)
ABSTRACTThis community engagement project focuses on strengthening legal capacity in rural communities through paralegal training in Molamahu Village, Pulubala District, Gorontalo Regency. The program was initiated to address the limited access of rural communities to legal aid due to low legal literacy, distance from formal institutions, and the shortage of lawyers in rural areas. The training employed a participatory approach, including basic legal education, case simulations, and direct mentoring. The findings reveal that paralegal training significantly improves community legal awareness, strengthens public participation in dispute resolution, and fosters the establishment of local legal discussion forums. Village paralegals have proven to be agents of change, bridging communities with the formal legal system while cultivating a restorative and participatory legal culture. This program is recommended for sustainable development through collaboration with legal aid institutions, universities, and village governments to enhance its effectiveness in expanding community access to justice.Keywords : Paralegal, access to justice, law enforcement